Gestión operativa en el área de descarga de pesca del puerto nacional de la ciudad de Manta - Merchan Baque, Wagner Efrain (2021)
The main objective of the research was to analyze the fishing unloading area of the national port of Manta as a contribution to the improvement of operational management, for its fulfillment a theoretical framework was developed that served as support to begin the investigation , this titling project was executed in the national port of Manta located on Avenida Malecón Jaime Chávez Gutiérrez and Calle 20, with a duration of nine months from its presentation, the study population was 120 owners of the fleets that use the port, as techniques the interview, survey, SWOT analysis, combined matrix, EFI and EFE matrices were applied, observation file and Delphi method, exploratory, descriptive, field and documentary investigations were carried out, the methods used were the following: inductive, deductive and analytical, as tools the observation guide was used, interview guide, questionnaire, Likert scale, improvement plan, 5w 1h matrix, cause-effect diagram and spss program, the most relevant problems in the fishing terminal were: lack of machinery (external cranes and forklifts), lack of basic services, damage to the access road, ignorance of the isps and basc codes, and in addition to this, there are problems when assigning fishing between artisanal shipments and industrial vessels. For this reason, the improvement plan served as a proposed solution to these problems and therefore contributed to the improvement of operational management in the port specifically in the area of fishing unloading.